2018
DOI: 10.18203/2349-3291.ijcp20183368
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical profile of human milk donors and their infants in a model human milk bank: a descriptive cross-sectional study

Abstract: Background: Human milk banking depends on donations and characterization of donors seems important. We aimed to determine prevalence of human milk donors and profile of regular donors and their infants.Methods: Cross-sectional study done on human milk donors in model HMB in tertiary NICU for six months.  Donors who had donated for more than 30% of their hospital stay considered as regular donors. Their sociodemographic and clinical profile along with their infant status recorded from history, examination and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(20 reference statements)
2
2
0
Order By: Relevance
“…Unexpectedly, some South African Muslims favored human milk donation. This was in keeping with researchers’ reports from India and Nigeria, where Muslim participants were willing to donate, emphasizing the diversity of religious beliefs (Balachandran et al, 2018; Iloh et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Unexpectedly, some South African Muslims favored human milk donation. This was in keeping with researchers’ reports from India and Nigeria, where Muslim participants were willing to donate, emphasizing the diversity of religious beliefs (Balachandran et al, 2018; Iloh et al, 2018).…”
Section: Discussionsupporting
confidence: 81%
“…The donor pool in South Africa is severely limited by low rates of breastfeeding (Goodfellow et al, 2016) and the high prevalence of the Human Immunodeficiency Virus (HIV), hence adequate characterization of donors is important (Balachandran et al, 2018; Stats SA, 2018). Factors that encourage mothers to donate, and to continue donating, need to be identified and appraised (Pimenteira Thomaz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…9 This could be explained by the fact that mothers who had already had other children, had already received assistance in feeding their babies, and had previously been reassured about the characteristics of their milk, quantity and quality. 7 Vaginal delivery was the most frequent, at 86%, similar to what was found in Ethiopia. 3 The initiation of breastfeeding is compromised by caesarean section.…”
Section: Demographic Profile Of Female Donorssupporting
confidence: 71%
“…In terms of the employment status of donors, the majority of mothers were housewives, i.e., 54.68%, which was also found by Balachandran et al in India (75.12%). 7 Housewives may have more time to donate milk than working mothers. In Bordeaux, Hitte et al showed that lack of time was an obstacle to milk donation.…”
Section: Demographic Profile Of Female Donorsmentioning
confidence: 99%